Implementasi Nilai-Nilai Kebangsaan yang Bersumber UUD 1945 dan NKRI dalam Mengacu Peran Manajemen Sekuriti Menunjang Keamanan Data Nasabah di Era Digital pada PT Bank Rakyat Indonesia - Della Fitri; Edy Soesanto; Winny Winny (Institut Nalanda, 2024)
Supporting customer data security in the digital era requires implementing the values ​​of the 1945 Constitution in relation to the Banking Basic Law and the Indonesian Banking Constitution. According to Article 40 paragraph (1) of Law of the Republic of Indonesia Number 10 of 1998 concerning Amendments to Banking Law Number 7 of 1998, banks are obliged to keep information regarding depositors and their deposits confidential, unless otherwise specified as follows: Mandatory. Sections 41, 41A, 42, 43, 44 and 44A. In this digital era, Bank BRI utilizes technology to serve its customers in the form of mobile banking services, namely the BRImo application. Mobile banking makes it easy for customers to carry out transactions safely and quickly. Therefore, banks need to improve their services, especially in the area of ​​customer data security, to face the current challenges of cybercrime, maintain customer trust, and contribute to supporting national security. The purpose of this research is to determine the role of security controls in maintaining customer data security and supporting national security. The method used is a literature review where data is collected through articles, books and related research reports. The findings show that security management plays an important role in maintaining the security of customer data by maintaining customer trust and implementing national values ​​that support Masu's national security.